Semantic information extraction from Tamil documents. (2nd March 2009) - Pandian, S. Lakshmana; Devakumar, J.; Geetha, T.V.
Semantic information extraction is a process of extracting concepts, entities, relations and entailment rules from a document. We propose an approach to extract concepts, entities and relations from the domain specific Tamil textual documents corpus. Concepts are extracted out by identifying semantic relationship between unique terms in documents by lexical database namely WordNet. Entity extraction process identifies proper names and its predefined named entity categories. Relation between two entities or between two concepts or between concept and entity in each sentence are extracted. This extracted semantic knowledge is exploited as a resource for extracting semantic information from the domain-related documents.